Effect of thermocycling on tensile bond strength of autopolymerized, heat-polymerized, milled, and 3D printed denture base materials bonded to 4 different denture liners: an in vitro study - Pilipda Janyaprasert; Krid Kamonkhantikul; Woraporn Homsiang; Mansuang Arksornnukit (BMC, 2024)
Abstract Background Digitally fabricated dentures may require relining due to continual alveolar ridge resorption. However, studies evaluating the tensile bond strength (TBS) of digitally fabricated dentures bonded to denture liners are lacking. This study aimed to evaluate the TBS of autopolymerized, heat-polymerized, milled, and 3D printed denture base materials bonded to 2 acrylic-based and 2 silicone-based denture liners, both before and after thermocycling. Additionally, the impact of thermocycling on the TBS were also evaluated. Methods The TBS of 4 different denture base materials (Palapress (PL), Vertex Rapid Simplified (VR), Smile CAM total prosthesis (SC), and NextDent denture 3D+ (ND)) bonded to 2 acrylic-based (GC Soft-Liner (GC) and Tokuyama Rebase II (RB)) and 2 silicone-based (Ufi Gel P (UP) and Sofreliner Tough M (ST)) denture liners were tested. Specimens (n = 8) were divided into non-thermocycling and thermocycling groups. Non-thermocycling specimens were tested after 24-hours water immersion, while thermocycling specimens were underwent 5000 cycle and were immediately tested. Mode of failure was examined under a stereomicroscope. Data were analyzed using 2-way ANOVA and Tukey HSD tests (α = 0.05), and independent samples t test (α = 0.05) for TBS between non-thermocycling and thermocycling groups. Results For the non-thermocycling groups, within the same denture liner material, no significant differences were found between denture base materials, except the ND + RB group, which had significantly lower TBS. For the thermocycling groups, within the same denture liner material, the TBS in the PL group exhibited the highest and the ND group exhibited the lowest. Within the same denture base material, in both non-thermocycling and thermocycling groups, the TBS in the ST group exhibited the highest; in contrast, that in the GC group exhibited the lowest. No significant differences were observed in TBS between non-thermocycling and thermocycling groups, except for denture base materials bonded to the ST group, SC + UP, and ND + UP groups. Conclusions Milled denture base can be relined with acrylic-based or silicone-based denture liner. However, cautions should be exercised when relining 3D printed denture base. Thermocycling did not affect TBS between acrylic-based denture liners and denture bases. In contrast, it affected the bond between silicone-based denture liner and denture base.